The Codification of Islamic Criminal Law in the Sudan: Penal Codes and Supreme Court Case Law Under Numayrī and al-Bashīr by Olaf Köndgen (American Journal of Islam and Society, 2020)
This meticulous work covers the history of legislation during two eras of military juntas in the Sudan: that of Numayrī, who led a coup against the democratic government and ruled from May 1969-April 1985, and of Bashir, who also came to power through a military coup and ruled the country from 1989-2018. This book was published just one year before a popular uprising brought down Bashir’s government. In his search to uncover the politics around Islamic codes, Köndgen used both primary and secondary sources, including court cases he closely reviewed, as well as interviews with lawyers and judges. This book is the most extensive study on the recent Islamic laws in the Sudan.To read the full book review, download the PDF file on the right.